Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1090/s0002-9947-07-04223-7
|View full text |Cite
|
Sign up to set email alerts
|

Intransitive Cartesian decompositions preserved by innately transitive permutation groups

Abstract: Abstract. A permutation group is innately transitive if it has a transitive minimal normal subgroup, which is referred to as a plinth. We study the class of finite, innately transitive permutation groups that can be embedded into wreath products in product action. This investigation is carried out by observing that such a wreath product preserves a natural Cartesian decomposition of the underlying set. Previously we classified the possible embeddings in the case where the innately transitive group projects ont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 17 publications
(19 reference statements)
0
7
0
Order By: Relevance
“…https://doi.org/10.1017/S1446788712000110 132 C. E. Praeger and C. Schneider [6] (d) (ϑ, χ) is a permutational embedding of X on Π into the group Sym Ω 0 × Sym Ω 1 in its product action on Ω 0 × Ω 1 , and Xχ ≤ W 0 × W 1 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…https://doi.org/10.1017/S1446788712000110 132 C. E. Praeger and C. Schneider [6] (d) (ϑ, χ) is a permutational embedding of X on Π into the group Sym Ω 0 × Sym Ω 1 in its product action on Ω 0 × Ω 1 , and Xχ ≤ W 0 × W 1 .…”
Section: Introductionmentioning
confidence: 99%
“…2] or [8, Sections 1.10 and 4.3]) and finite quasiprimitive groups [13]. They have received special attention recently in the work of Aschbacher [1,2] aimed at studying intervals in subgroup lattices [3] (with Shareshian), and of the authors [4][5][6]14] action of the wreath product W = Sym Γ Sym ∆ is its natural action on the set Π = Func(∆, Γ) of functions from ∆ to Γ, described in Section 1.1. If ∆ = {1, .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lifting the restriction that the socle should be simple, we found that the variety of possible inclusions (of quasiprimitive groups in wreath products in product action) far outstripped anything we could have imagined. We developed a theory of such inclusions and many of the details of this theory are described in [3][4][5]18]. Our theory can be viewed as a generalisation of Baumeister's results [7], which are concerned with the subgroups G of S n S 2 such that G projects onto the top group S 2 and such that the projections of G on the two components of S n × S n are primitive and faithful.…”
Section: Introductionmentioning
confidence: 99%
“…k > 1 Transitive 6 types identified studied; further in [4,17,18] [5] k > 1 Intransitive Top group has two orbits; 5 types are identified product of smaller components. A Cartesian decomposition in which all the components have the same size is said to be homogeneous.…”
Section: Introductionmentioning
confidence: 99%